Analysis of natural convection flows of Jeffrey fluid with Prabhakar-like thermal transport. (July 2022) - Khan, Zar Ali; Shah, Nehad Ali; Haider, Nadeem; El-Zahar, Essam R.; Yook, Se-Jin
Abstract: The free convection flow of Prabhakar fractional Jeffrey fluid on an oscillated vertical plate with homogenous heat flux is investigated. With the help of the Laplace transform and the Boussinesq's approximation, precise solutions for dimensionless momentum may be found. The temperature and velocity of Prabhakar fractional time free convection flows are compared to conventional thermal transport, as shown by Fourier's law. They met all of the requirements and recovered Newtonian and ordinary Jeffrey fluid solutions from fractional Jeffrey fluid. Finally, graphs show the effect of various physical parameters such as fractional parameters, Grashof number, Prandtl number and Jeffrey parameters on both temperature and velocity.